Long COVID and Mental Health: Neurobiological Mechanisms, Clinical Manifestations, and Treatment Challenges - Sandra Kołodziejczyk; Bartłomiej Wiak; Monika Łapot; Wiktoria Raczek; Ernest Racki; Agata Wywiał; Klaudia Spaczyńska; Anna Kropiwnicka; Yassine Motaouakkil; Bartosz Mikołajek; Anna Kocik; Anita Godlewska; et al. (African Journal of Biomedical Research, 2026)
Background: Long COVID is a heterogeneous multisystem condition associated with fatigue, cognitive difficulties, sleep disturbance, depression, anxiety, and post-traumatic symptoms. Methods: This narrative review examined PubMed/MEDLINE literature published between January 2020 and July 2026, supplemented by major reviews and guidance from WHO, NICE, and CDC. Results: Neuropsychiatric symptoms likely result from interacting mechanisms, including persistent immune activation, autoimmunity, endothelial dysfunction, blood–brain barrier disruption, dysautonomia, altered neurotransmitter metabolism, microbiome changes, and impaired cellular energy production. Routine investigations may be normal, and no diagnostic biomarker has been validated. Treatment remains multidisciplinary, symptom-based, and tailored to clinical phenotype, with rehabilitation adapted for post-exertional malaise. Conclusion: Long COVID requires integrated medical, neurological, and psychiatric assessment. Further biomarker-based research and well-designed clinical trials are needed.